Editorial: AABFJ Volume 9, Issue 1, 2015 - Monir Mir (Australasian Accounting, Business and Finance Journal, 2015)
There are six excellent and diversified papers published in this edition of the Australasian Accounting, Business and Finance Journal. As highlighted below, these papers’ contributions range from issues relating to accounting standard setting process to the efficient market hypothesis including a paper based on alternative accounting research methodology that explores the issues of career choices by women in a developing economy.
Keywords: Editorial AABFJ Volume 9 Issue 1